The Lys‐motif receptor LYK4 mediates Enterobacter sp. SA187 triggered salt tolerance in Arabidopsis thaliana. (23rd December 2021) - Rolli, Eleonora; de Zélicourt, Axel; Alzubaidy, Hanin; Karampelias, Michael; Parween, Sabiha; Rayapuram, Naganand; Han, Baoda; Froehlich, Katja; Abulfaraj, Aala A.; Alhoraibi, Hanna; Mariappan, Kiruthiga; Andrés‐Barrao, Cristina; et al.
Summary: Root endophytes establish beneficial interactions with plants, improving holobiont resilience and fitness, but how plant immunity accommodates beneficial microbes is poorly understood. The multi‐stress tolerance‐inducing endophyte Enterobacter sp. SA187 triggers a canonical immune response in Arabidopsis only at high bacterial dosage (>10 8  CFUs ml −1 ), suggesting that SA187 is able to evade or suppress the plant defence system at lower titres. Although SA187 flagellin epitopes are recognized by the FLS2 receptor, SA187‐triggered salt tolerance functions independently of the FLS2 system. In contrast, overexpression of the chitin receptor components LYK4 and LYK5 compromised the beneficial effect of SA187 on Arabidopsis, while it was enhanced in lyk4 mutant plants. Transcriptome analysis revealed that the role of LYK4 is intertwined with a function in remodelling defence responses with growth and root developmental processes. LYK4 interferes with modification of plant ethylene homeostasis by Enterobacter SA187 to boost salt stress resistance. Collectively, these results contribute to unlock the crosstalk between components of the plant immune system and beneficial microbes and point to a new role for the Lys‐motif receptor LYK4 in beneficial plant–microbe interaction.